IMPLEMENTASI PENGGUNAAN RAPOR DIGITAL MADRASAH (RDM) BERBASIS ONLINE DALAM MENYUSUN ADMINISTRASI PENILAIAN HASIL BELAJAR PESERTA DIDIK - Nidaul Fajrin; Imam Machali (Idaarah: Jurnal Manajemen Pendidikan, 2023)
This research study aims to provide a description related to the ease and mastery of MI PUI Kaum teachers in using digital madrasah report cards online. Obtain data by conducting interviews, observations and documentation. The research subjects were selected according to the 3M criteria (Knowing, Understanding, Experiencing) namely the head of madrasah, deputy curriculum, operator and homeroom teacher. The research location chosen was the Banjarsari Islamic Community Association Madrasah Ibtidaiyah, this location was chosen because the MI had just implemented the RDM application in the 2021/2022 school year. The results showed that the use of online-based digital madrasah report cards was more effective than conventional report cards and reports on Microsoft Excel. This can be concluded based on the convenience of the homeroom teacher in inputting student scores through the template provided on the RDM website then only needing to upload the template and then the student learning outcomes will appear.